Factors affecting climate in Africa - Okic Yor, Angelo (IJRDO Journal of History & Geography, 2021)
The study is focused on the background of climate. It also aimed to discuss the factors affecting climate in Africa. It is also wanted to describe the location of Africa, the physical features of Africa such as climate, soil, and natural vegetation. In the same time, the paper concentrate on population of Africa, their countries in Africa. Moreover, the study cover the size and shape of the Africa’s continent. The study used primary and secondary source to obtain data collection. Also, the qualitative and quantitative descriptive methods was employed for a finding of factors affecting climate in Africa. On the same way, the study recommended to the researchers to emphasis on availing complete information about the factors affecting climate in Africa.